Nurse Jackie. Season three [videorecording (DVD)] - Brixius, Liz; Wallem, Linda, 1961-; Dunsky, Evan, 1957- (Lions Gate Home Entertainment, 2012)
Jackie's best friend and husband put the pieces together about her pill-popping ways and confront her about her addiction. But if the people in her life think one little intervention is going to stop her, they don't know Jackie. The great white liar returns for another hilarious season of 12 episodes.